Covid-19 and Therapeutic Options for its Clinical Management: A Narrative Review (Bangladesh Journal of Infectious Diseases, 2023)
COVID- 19 caused by SARS-CoV-2 was declared a pandemic by the WHO on 11th March 2020. In Bangladesh, confirmed COVID-19 cases were detected on March 8, 2020 and since then, Bangladesh is also facing the toll of this highly transmissible viral infection. Though the main strategy to handle the pandemic is containment by isolation of cases, quarantine of contacts, physical distancing of people, wearing masks and sanitizing hand and other sources of contamination, the potential severity of the disease and its deadly complications require effective clinical management as well. In addition to optimized supportive and symptomatic therapy, drugs targeting the pathogenesis of this viral infection at different levels can be proved efficacious in COVID-19. Keeping this in mind, different anti-viral drugs which had been found effective in some pre-clinical and clinical studies against other viruses have been used against SARS-CoV-2. Immunomodulatory and anti-thrombotic agents have proved their own place in treating COVID-19 targeting SARS-CoV-2 induced cytokine storm and hypercoagulability. Some drugs used mainly against protozoal infection have also been used by the virtue of their additional antiviral property. Use of vitamins and minerals to boost up the immunity is also widespread. This review provides an overview of current COVID-19 status, its ways of transmission and clinical presentation. Discussing the pathophysiology, the review explores how drugs used for the purpose of treating COVID- 19 can modulate various stages and factors resulting beneficial outcome. Categorization of COVID-19 cases and their severity-wise management in perspective of Bangladesh have also been discussed. Drugs using worldwide and in Bangladesh have been overviewed in this review justifying their recommendation against SARS-CoV-2.Bangladesh Journal of Infectious Diseases, June 2023;10(1):38-51